2013
DOI: 10.1186/1475-925x-12-84
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing conditioned roughness and wear of biomedical oxide ceramics for all-ceramic knee implants

Abstract: BackgroundCeramic materials are used in a growing proportion of hip joint prostheses due to their wear resistance and biocompatibility properties. However, ceramics have not been applied successfully in total knee joint endoprostheses to date. One reason for this is that with strict surface quality requirements, there are significant challenges with regard to machining. High-toughness bioceramics can only be machined by grinding and polishing processes. The aim of this study was to develop an automated process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
0
8
0
1
Order By: Relevance
“…Generally, the milled conventional orthopaedics joints are subjected to a serious of grinding processes by machines with three or more axes [114]. Polishing is employed as the last step to achieve desired smooth surfaces, where the manual process is often involved [115,116].…”
Section: Surface Finishing Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the milled conventional orthopaedics joints are subjected to a serious of grinding processes by machines with three or more axes [114]. Polishing is employed as the last step to achieve desired smooth surfaces, where the manual process is often involved [115,116].…”
Section: Surface Finishing Processesmentioning
confidence: 99%
“…Therefore, precise grinding and polishing processes must be applied to ensure the material removal mode maintains in the ductile region. It is reported that there are about 60 individual machining steps required for even the relatively simple geometry of a ceramic hip replacement [114]. In contrast to hip implant components, the artificial knee joint has more complex and partly freeform surfaces, which raises the difficulty of manufacturing.…”
Section: Surface Finishing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that this technology is a simplified model of normal walking, and simulation of the motion and loading in activity is very limited. In fact, there are three complicated articulation mechanisms that are involved in the motion of a tibiofemoral joint, namely gliding, pure rolling and rolling-slipping [129]. Investigations are required to elucidate the complex environment of the host body and increased patient activities.…”
Section: Wear Testsmentioning
confidence: 99%
“…They can measure both form and surface roughness in one scan with a vertical resolution of approximately 1 nm and a resolution across the contacting surfaces of approximately 1 µm. Non-contacting optical methods such as white light interferometry 11,17 and laser confocal profilometry 18 have been successfully used to measure the volumetric wear of ceramic hip and knee implants. They also have the advantage over the gravimetric method that the pattern of wear across the implant surface can be seen and areas of severe wear identified.…”
mentioning
confidence: 99%